Thou shalt have no other gods before me: why governments discriminate against religious minorities - Fox, Jonathan (Cambridge University Press, 2020)
"This book is among the most thorough and comprehensive analysis of the causes of religious discrimination to date, complete with detailed illustrations and anecdotes. Jonathan Fox examines the causes of government-based religious discrimination (GRD) against 771 minorities in 183 countries over the course of twenty-five years, while offering possible reasons for why some minorities are discriminated against more than others. Fox illustrates the complexities inherent in the causes of GRD, which can emerge from secular ideologies, religious monopolies, anti-cult policies, security concerns and more. Western democracies tend to discriminate more than Christian-majority countries in the developing world, whether they are democratic or not. While the causes of GRD are ubiquitous, they play out in vastly different ways across world regions and religious traditions. This book serves as a method for better understanding this particular form of discrimination, so that we may have the tools to better combat it and foster compassion across people of different religions and cultures"--